Design and analysis of digital control buck converter for optimum performance - Elisa Razali, Nur Ain; Alam, AHM Zahirul (AlamBiblio Publishers, 2025)
This paper aims to design and analyze a digitally controlled buck converter meant for applications requiring DC voltage under varying input voltages and load conditions. The buck converter is designed with a switching frequency of 40 kHz, an inductor value of 200 µH, and a capacitor of 100 µF with Pulse Width Modulation (PWM). The Proportional-Integral (PI) controller is used to maintain the output voltage steady. For simulation and performance evaluation, PSpice and MATLAB/Simulink software are selected. This paper aims to create a digital control system that is better than the traditional analog controllers, offering precise and adaptive regulation. The simulation results highlight how effective the digital PI controller is at reducing voltage ripple and maintaining the output voltage, even when the inputs and loads vary. This study covers detailed parameter calculations, controller design, circuit simulation, and performance analysis, providing a thorough overview of the digitally controlled buck converter system